2021
DOI: 10.1101/2021.02.14.21251708
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of January 2021 curfew measures on SARS-CoV-2 B.1.1.7 circulation in France

Abstract: Facing B.1.1.7 variant, social distancing was strengthened in France in January 2021. Using a 2-strain mathematical model calibrated on genomic surveillance, we estimated that social distancing allowed hospitalizations to plateau, by decreasing transmission of the historical strain while B.1.1.7 continued to grow. Variant dominance is expected by the end of February-early March in France, with large geographical heterogeneity. Without strengthened social distancing, a rapid surge of hospitalizations is expecte… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 32 publications
3
30
0
Order By: Relevance
“…In parallel, mathematical models anticipate how the rise of 501Y.V1 and other variants may affect the course of the pandemic and the impact of control measures [9,10]. It will also be important to determine how spatial heterogeneities in the spread of variants may affect control strategies.…”
Section: Discussionmentioning
confidence: 99%
“…In parallel, mathematical models anticipate how the rise of 501Y.V1 and other variants may affect the course of the pandemic and the impact of control measures [9,10]. It will also be important to determine how spatial heterogeneities in the spread of variants may affect control strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Seven studies contributed data which may be relevant to modifying the current approach to vaccine scheduling and delivery (see Table 1). Of the seven studies, 5 were modeling [40][41][42] or lab-based studies 43,44 which were not critically appraised. The two studies that were critically apprised were of low quality.…”
Section: Critical Appraisalmentioning
confidence: 99%
“…Domenico et al used a discrete, stochastic model integrating demography, age profile, social contacts, and mobility data over time to model the impact of social distancing measures on two strains of SARS-CoV-2 (historical, B.1.1.7). 40 Strain circulation dynamics for France, Ile-de-France regions and Nouvelle Aquitaine were secured through Santé Publique France on January 28, 2021. The model estimated that the progressive social distancing implemented in January 2021 brought the reproductive number of the historical strain below 1 but the B.1.1.7 cases increased exponentially with the estimated reproduction (R) about 1 in all three regions.…”
Section: Physical Distancingmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have tried to estimate the relative strength of the novel variant from the observed relative speed (Davies et al, 2021;Leung et al, 2021;Volz et al, 2021;Zhao et al, 2021). Some studies have instead assumed a value of the relative strength of the novel variant and tried to predict its relative speed to determine when a new variant will become the dominant strain (Davies et al, 2021;Di Domenico et al, 2021).…”
Section: Introductionmentioning
confidence: 99%